2010
DOI: 10.1128/iai.00813-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trehalose Biosynthesis in Aspergillus fumigatus Development, Stress Response, and Virulence

Abstract: Aspergillus fumigatus is a pathogenic mold which causes invasive, often fatal, pulmonary disease in immunocompromised individuals. Recently, proteins involved in the biosynthesis of trehalose have been linked with virulence in other pathogenic fungi. We found that the trehalose content increased during the developmental life cycle of A. fumigatus, throughout which putative trehalose synthase genes tpsA and tpsB were significantly expressed. The trehalose content of A. fumigatus hyphae also increased after heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
128
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 48 publications
(77 reference statements)
8
128
1
Order By: Relevance
“…EUKARYOT. CELL mutants all induced an exaggerated host inflammatory response (1,9,18). Collectively, these results suggest that the composition of the cell wall plays a key role in determining the host inflammatory response to and virulence of A. fumigatus.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…EUKARYOT. CELL mutants all induced an exaggerated host inflammatory response (1,9,18). Collectively, these results suggest that the composition of the cell wall plays a key role in determining the host inflammatory response to and virulence of A. fumigatus.…”
mentioning
confidence: 70%
“…The deletion of ace2, ags3, and ecm33 is associated with enhanced virulence in murine models of invasive pulmonary aspergillosis (9,18,31). Recently we reported that an A. fumigatus double mutant lacking the trehalose biosynthesis genes tpsA and tpsB also was hypervirulent in mice (1). This mutant had the reduced expression of ags3, suggesting that a reduction in cell wall ␣(1-3)glucans contributed to its hypervirulent phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquisition of osmoprotectants is important for the survival of the conidia and for mycelial growth of filamentous fungal pathogens such as Aspergillus fumigatus in their human host (8,9). However, the mechanisms controlling the osmotic pressure changes during the biological cycle of fungal species remain insufficiently understood.…”
mentioning
confidence: 99%
“…However, the mechanisms controlling the osmotic pressure changes during the biological cycle of fungal species remain insufficiently understood. Although trehalose has been repeatedly cited as the major metabolite involved in the osmoprotection of A. fumigatus, several arguments suggest that it is not the only one: (i) trehalose is rapidly degraded upon induction of conidial germination and increases again later during mycelial growth; (ii) two metabolic pathways for the biosynthesis of trehalose have been identified, but their respective roles have not been evaluated; and (iii) other polyols have been also suggested to be associated with changes in osmotic pressure (8,9). This also raised the question of the existence of other molecules that could be associated with osmoprotection during the fungal biological cycle.…”
mentioning
confidence: 99%